2019
DOI: 10.1042/bcj20180680
|View full text |Cite
|
Sign up to set email alerts
|

Ribavirin-induced down-regulation of CCAAT/enhancer-binding protein α leads to suppression of lipogenesis

Abstract: Recently, we demonstrated that the anti-viral drug ribavirin (RBV) had the ability to suppress lipogenesis through down-regulation of retinoid X receptor α (RXRα) under the control of the intracellular GTP-level and AMP-activated protein kinase-related kinases, especially microtubule affinity regulating kinase 4 (MARK4). RXRα-overexpression attenuated but did not abolish lipogenesis suppression by RBV, implying that additional factor(s) were involved in this suppressive effect. In the present study, we found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Here, we used RNA-seq to identify the regulatory networks of mRNAs and noncoding RNAs in breast cancer. Among the results from the analysis of potential mRNA interactions, MARK4 sparked our interest since it is associated with tumorigenesis [49,50]. Previous studies showed that MARK4 attenuates the proliferation and migration of MDA-MB-231 cells via the Hippo signaling pathway [39].…”
Section: Discussionmentioning
confidence: 99%
“…Here, we used RNA-seq to identify the regulatory networks of mRNAs and noncoding RNAs in breast cancer. Among the results from the analysis of potential mRNA interactions, MARK4 sparked our interest since it is associated with tumorigenesis [49,50]. Previous studies showed that MARK4 attenuates the proliferation and migration of MDA-MB-231 cells via the Hippo signaling pathway [39].…”
Section: Discussionmentioning
confidence: 99%
“…To address the mechanisms by which ERRa regulates the expression of these genes involved in glycerolipid synthesis, the role of C/EBPb was explored, as GPAT1, DGAT1, and DGAT2 are transcriptional targets of C/EBPb. 38,39 Consistent with a positive regulatory role of C/EBPb on the transcription of GPAT1 and DGAT2, expression of exogenous C/EBPb in Huh7 cells led to their induction compared with the untreated vector controls (Figure 6A). Although inhibiting ERRa with ERR-PA reduces the expression of GPAT1 and DGAT2, introduction of C/EBPb blocks this effect.…”
Section: Regulation Of Gpat1 Dgat1 and Dgat2 But Not Gpat4 By C/ebpbsupporting
confidence: 58%
“…Similarly, inhibition of FASN with C75 reduced HCV replication in vitro (88). Other evidence suggests that currently used anti-HCV agents like ribavirin inhibit lipogenesis as a side effect, which may contribute to their antiviral properties (95, 96). Mechanistically, ribavirin suppresses the expression of lipogenic genes such as SREBP-1c, FASN, and SCD-1 in a retinoid X receptor α- and CCAAT/enhancer-binding protein α-dependent manner (95, 96).…”
Section: Viral Control Of Fatty Acid Metabolismmentioning
confidence: 99%
“…Other evidence suggests that currently used anti-HCV agents like ribavirin inhibit lipogenesis as a side effect, which may contribute to their antiviral properties (95, 96). Mechanistically, ribavirin suppresses the expression of lipogenic genes such as SREBP-1c, FASN, and SCD-1 in a retinoid X receptor α- and CCAAT/enhancer-binding protein α-dependent manner (95, 96). Statins, another class of drugs used in a wide number of patients due to their cholesterol- and lipid-lowering properties, exhibited an inhibitory effect on HCV replication probably due to the inhibition of the rate-limiting step of the mevalonate pathway, 3-hydroxy3-methyl-glutaryl coenzyme A reductase (HMG-CoA reductase) (97, 98).…”
Section: Viral Control Of Fatty Acid Metabolismmentioning
confidence: 99%